Case report: Fatal infantile hypertonic myofibrillar myopathy with compound heterozygous mutations in the CRYAB gene - Zhang, Shan-shan; Gu, Li-niu; Zhang, Teng; Xu, Lu; Wei, Xiang; Chen, Su-hong; Shi, Su-jie; Sun, Da-quan; Zhou, Shao-hong; Zhao, Qian-ye (Frontiers in Pediatrics, 2023)
We report a case of fatal infantile hypertonic myofibromyopathy (FIHMM) with a novel heterozygous missense mutation in the CRYAB gene. This patient was a 2-year-old female who developed scoliosis of the lumbar spine and restrictive ventilatory dysfunction in infancy. She was admitted into hospital with labored breathing on the third day after a second injection of inactivated poliomyelitis vaccine. Acute respiratory failure, pneumothorax, and cardiac arrest arose during hospitalization, and progressive stiffness of the trunk and limbs muscle appeared, accompanied by obvious abdominal distension and an increase in phosphocreatine kinase levels. Electromyography revealed mild myogenic damage. A muscle biopsy showed the accumulation of desmin, α-crystallin, and myotilin in the musculus biceps brachii, and dense granules were observed in muscle fibers using electron microscopy. Mutation analysis of CRYAB revealed novel and de novo heterozygous missense mutations, C.3G > A (p.M1I) and c.302A > C (p.H101P), through which we were able to diagnose the patient with FIHMM. One month after the FIHMM diagnosis, the child died of irreversible respiratory failure. These findings improve our understanding of FIHMM and highlight a de novo mutation in the Chinese population.